Evaluation of the efficiency of antibiotics in treating adult patients with symptomatic apical periodontitis: A protocol for systematic review and meta-analysis. Issue 25 (25th June 2021) - Luo, Wenping; Yan, Huifen; Guo, Sijie
Abstract: Background: When a person feels dental pain, it brings great discomfort and damages the quality of life. Symptomatic apical periodontitis is identified as the most frequent cause that triggers dental pain. Symptomatic apical periodontitis arises from an infection or inflammation in the pulpless root canal structure. According to clinical guidelines, the primary form of therapy for such teeth entails removing the inflammation or infection source through local surgical procedures. Presently, systemic antibiotics are recommended only for cases where there is clear indication of an infectious spread or a systemic involvement. Therefore, this study aims to assess the efficacy and level of safety of using antibiotics to treat adult symptomatic apical periodontitis patients. Methods: The present protocol study will conduct a search on electronic databases to look for randomized controlled trials (RCTs) that have evaluated the effectiveness and safety of antibiotics when used to treat adult patients with symptomatic apical periodontitis. The databases will be search from their beginning to April 2021. The search is not bound by publication status or language restrictions. The following databases will be searched: Web of Science, PubMed, the Cochrane Library, Chinese National Knowledge Infrastructure, and EMBASE. This study will employ ZETOC Conference Proceedings and OpenGrey to identify potential grey literature. Afterwards, 2 independent authors will select the studies, extract data from the studies, and conduct a risk assessment to check for bias. All discrepancies between the authors will be resolute via discussion involving a third independent author. The data synthesis and statistical analysis of this study will be done with the RevMan software (Version: 5.3). Results: The present protocol report will provide high-quality evidence related to the efficacy and level of safety when using antibiotics to treat mature symptomatic apical periodontitis patients. Conclusion: The outcomes of the present study will update the evidence available for assessing the efficacy and safeness of using antibiotics to treat mature symptomatic apical periodontitis patients. Ethics and dissemination: This study does not require an ethical approval since individual patient data is not included in any form. Registration number: DOI 10.17605/OSF.IO/CVP8 M (https://osf.io/cvp8m/ ).